Seistenism – a new look at the concept of sustainable building - Skakun, V. (Ways to Improve Construction Efficiency, 2024)
The article examines the current state of the implementation of sustainable development approaches in construction enterprises and construction projects, and also considers construction from the perspective of Seistenism. Seistenism is a new concept in economic development and construction that focuses on sustainable, efficient and technologically integrated construction practices. This concept combines building principles and approaches from various disciplines, including architecture, construction and civil engineering, ecology, environmental economics and environmental science, to create a structure that is not only functionally and aesthetically appealing, but also environmentally responsible and sustainable. to changing climatic conditions, while ensuring economic efficiency and minimal impact on the environment. Key elements of Seistenism include the use of renewable materials, energy-efficient designs, and integrated smart technologies to optimize building performance. The concept advocates a holistic approach to construction, which takes into account the entire life cycle of a building, from design and construction to operation and final dismantling of building structures and liquidation of the facility. This approach aims to minimize the impact of buildings on the environment, reduce resource consumption and promote the health and well-being of residents. In addition, Seistenism emphasizes the importance of community involvement and the inclusion of local cultural and environmental contexts in the design process. By fostering collaboration between stakeholders, including architects, engineers, developers and the community, systemicism involves creating buildings that are not only sustainable, but also culturally relevant and economically viable. Applying systemic principles to construction can lead to significant progress in the industry, fostering innovation and encouraging the widespread adoption of sustainable practices. Ultimately, Seistenism represents an advanced approach to construction that aligns with global efforts to combat climate change and promote sustainable development.